2007
DOI: 10.1128/jvi.00408-07
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Brd4/P-TEFb Interaction by the Human T-Lymphotropic Virus Type 1 Tax Protein

Abstract: Positive transcription elongation factor (P-TEFb), which is composed of CDK9 and cyclin T1, plays an important role in cellular and viral gene expression. Our lab has recently demonstrated that P-TEFb is required for Tax transactivation of the viral long terminal repeat (LTR). P-TEFb is found in two major complexes: the inactive form, which is associated with inhibitory subunits 7SK snRNA and HEXIM1, and the active form, which is associated with, at least in part, Brd4. In this study, we analyzed the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
(68 reference statements)
2
34
0
Order By: Relevance
“…A peptide derived from the C-terminal domain of Brd4 L can inhibit Tat-mediated transcription (7). Similarly, HTLV-I Tax and Brd4 compete for binding to pTEF (10). In this work, we demonstrated that MHV-68, the only available small-animal model for gamma-2 herpesvirus infection and pathogenesis, also interacts with the BET proteins Brd2, Brd3, and Brd4 via its orf73 protein, the LANA-1 homolog.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A peptide derived from the C-terminal domain of Brd4 L can inhibit Tat-mediated transcription (7). Similarly, HTLV-I Tax and Brd4 compete for binding to pTEF (10). In this work, we demonstrated that MHV-68, the only available small-animal model for gamma-2 herpesvirus infection and pathogenesis, also interacts with the BET proteins Brd2, Brd3, and Brd4 via its orf73 protein, the LANA-1 homolog.…”
Section: Discussionmentioning
confidence: 79%
“…There are a number of different ways in which pTEFb can be recruited to transcription complexes, and the recruitment via the chromatin-bound activator Brd4 is one of them (46). HTLV-1 has recently been shown to modulate the Brd4/pTEFb interaction through the interaction of its Tax protein with the cyclin T1 subunit of pTEFb, thereby possibly competing with the Brd4/pTEFb interaction (10). Similarly, Brd4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different viruses target the individual BET proteins for a variety of purposes but often to regulate viral and cellular transcription (4,7,31,37,41,45,57,60). The papillomavirus E2 proteins bind to Brd4, and some utilize this interaction in tethering the viral genomes to mitotic chromosomes (1,3,57,59).…”
mentioning
confidence: 99%
“…In addition, cdk9 plays an integral role in p53 phosphorylation during Kaposi's sarcoma-associated herpesvirus infection via cdk9 interaction with a virus-encoded cyclin (11). P-TEFb activity is also modulated through Brd4 during human T-cell leukemia virus infection (12,55).…”
Section: Discussionmentioning
confidence: 99%